Handbook of hydraulics for the solution of hydraulic engineering - Brater, Ernest F., 11912-2003. (McGraw-Hill, 1996)
Fluid Properties and Hydraulic Units. |x Hydrostatics. |x Fundamental Concepts of Flow. |x Orifices, Gates, and Tables. |x Weirs. |x Pipes. |x Steady Uniform Flow in Open Channels. |x Open Channels with Non-Uniform Flow. |x High-Velocity Transitions. |x Wave Motion and Forces. |x Spatially Variable and Unsteady Flow. |x Measurement of Flowing Water. |x Advances in Hydraulics Using Computer Technology. |x Applicable Computer Programs. |x